Il nuovo arbitrato nel diritto del lavoro a seguito della riforma del "Collegato Lavoro" - Mangini, Giulia (Università di Pisa, 2016)
L' elaborato si propone l' obiettivo di analizzare le nuove tipologie arbitrali introdotte dalla legge n. 183/2010 e le loro probabilità di successo nell'ordinamento italiano. Per far ciò, prima di concentrarmi sulla attuale disciplina, ho proceduto ad una ricognizione storica dell' istituto arbitrale e dell' impianto normativo su cui il legislatore del 2010 è intervenuto. Infine ho svolto un' analisi di diritto comparato, prendendo a riferimento gli ordinamenti di USA ed Inghilterra e verificando come lì l' arbitrato ed in generale i metodi ADR, vengono utilizzati.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrato; Collegato lavoro; Diritto di lavoro; Droit du travail; Labour law; Travaux connexes

Analyse des causes des impayés dans le processus d'octroi de crédit dans les institutions de microfinance au Cameroun : cas de la Bourse d'Epargne et de Crédit (BEC) - Voukeng, Ghislain-Blaise (Université de Liège, 2016)
Microfinance institutions are specialized in the financing of economic activities of small sizes. They have a social role to target many excluded from the traditional financial system, including poor households, sole proprietorships, small and medium enterprises and mutual aid associations by offering to them suitable financial services (Kobou et al. 2009). In doing so, they are perceived by the vast majority of public opinion internationally as a useful lever for poverty reduction. They must nevertheless obtain sufficient economic and financial results to ensure their viability and sustainability. But in recent decades, there is a certain fragility of MFIs with cases of cascading bankruptcy in Cameroon, where one of the major causes of this bankruptcy remains the unpaid. This study examines the causes of the unpaid loan in the microcredit process in second category of microfinance institutions in Cameroon through the specific case of the "Bourse d’Epargne et de Credit" (BEC). To do this, a multi-variables analysis based on logistic regression method was performed on 195 individuals who have benefited the credit based on six factors, including the sex of the applicant (male or female), the socio professional category of applicant (trader, employee, and very small business-man), the credit period, the number of times an individual has benefited a credit, interest expenses borne by the applicant and the time to study and reply one credit demand. After analysis and discussion, it emerges that: the very small business-man, credit duration, the number of times an individual has benefited the loan; the interest charges borne by the customer are risk factors that increase the level of unpaid with a significant level of 5%. Other factors of the professional category (trader and employee); the credit applicant customer's gender (male or female) and the time to study and reply to a credit demand are factors that have low risk for unpaid. These factors are considered as protective factors of unpaid, also at the significant level of 5%. In addition, it also shows that certain portion of the target where credit is granted is unsuited to the context of the institution's objectives; there is a managerial problem in the structure in question.
Keywords: Credit; Microfinance institution; Risk; Sustainability; Unpaid loan

Desafios da harmonização do direito do comércio internacional - Boscolo, Ana Teresa de Abreu Coutinho (Universidade de São Paulo, 2016)
Trata-se de estudo sobre desafios existentes para a harmonização do direito do comércio internacional, entendendo-se harmonização de forma ampla, como busca da harmonia dos instrumentos e regras do comércio internacional. Dessa forma, o estudo trata tanto de questões de unificação quanto de harmonização do direito do comércio internacional. A harmonização, em sentido específico, deve ser entendida como a utilização de um instrumento como modelo ou fonte de inspiração para a elaboração ou interpretação de outros instrumentos ou dos direitos nacionais. A unificação, por sua vez, é entendida como o resultado da aplicação de um instrumento único de modo que o aplicador que a realizou seja indiferente. Nesse sentido, os desafios estão nos fatores que impedem o preenchimento dos requisitos que levam à unificação e à harmonização, quais sejam: elaboração dos instrumentos, entrada em vigor dos tratados, incorporação dos modelos aos direitos nacionais, aplicação dos instrumentos pelos aplicadores (árbitros e juízes), o que inclui questões relativas a regras de conflito de leis, normas imperativas e ordem pública, relação entre os instrumentos quando da sua elaboração e quando da sua aplicação.
Keywords: Arbitrage; Arbitragem; Arbitration; Comércio internacional; Conflict of laws; Direito internacional privado; Harmonization; Harmonização; International commerce; Unification; Unificação

La réforme du droit des contrats et la prise en compte de l’erreur en droit de la distribution - Rodriguez, Marion (Université de Perpignan Via Domitia, 2016)
Cette étude porte sur les modifications apportées par l’ordonnance du 10 février 2016 et notamment l’impact qu’elles devraient impliquer sur la théorie de l’erreur en tant que vice du consentement, entraînant un défaut dans les conditions de validité du contrat (article 1128 nouveau du Code civil). Sur cette seule notion, le changement est éloquent. Le Code civil actuel ne contient que deux dispositions relatives à l’erreur (article 1109 et 1110) et une jurisprudence foisonnante qui en détermine les contours alors que la réforme en prévoit dorénavant six (articles nouveaux 1130, 1132, 1133, 1134, 1135 et 1136). Cette modification quantitative a pour objectif de préciser les contours d’une notion dont le champ d’application est fortement discuté tant par les praticiens du droit que par les professionnels. Dans ce domaine du contrat de franchise, les difficultés liées à la prise en compte de l’erreur sur la rentabilité, c’est-à-dire du potentiel de chiffre d’affaires dégagé par l’exploitation d’un commerce, réside dans la nécessaire mise en balance des intérêts de chacune des parties. Nombreux ont été les franchisés à arguer d’une erreur sur la rentabilité ayant entraîné un vice de leur consentement au moment de la conclusion du contrat, afin de se délier d’un réseau de franchise jugé non rentable. Cependant, l’annulation du contrat ne peut revêtir la forme d’une épée de Damoclès au-dessus du franchiseur. Il est essentiel de trouver un équilibre afin de pouvoir, à la fois, protéger l’intégrité du consentement du franchisé et apporter une stabilité aux relations valablement conclues. À partir de ces multiples constatations, cette étude tentera d’appréhender la difficulté du droit positif et de l’ordonnance portant réforme du droit des contrats à élargir le champ d’application de l’erreur. En ce sens, la nouvelle définition de l’erreur sera-t-elle de nature à sonner le glas de la construction prétorienne reconnaissant l’erreur sur la rentabilité économique de l’activité entreprise comme source de nullité du contrat de franchise ? Afin d’y parvenir, l’analyse du renouvellement de la qualification de l’erreur (Partie 1) devrait permettre d’appréhender les raisons pour lesquelles la reconnaissance de l’erreur sur la rentabilité dite « objective » constitue un instrument au service de l’intégrité du consentement du franchisé (Partie 2).
Keywords: Droit de la distribution; Droit des contrats; Théorie de l'erreur

La réglementation du travail domestique au Bénin et les apports de la convention 189 de l'OIT - Ahonoukoun, Loren Violette (Université du Québec à Montréal, 2016)
L'étude que nous avons menée aborde la question de la protection juridique des travailleuses domestiques au Bénin. Les travailleuses domestiques au Bénin sont essentiellement de jeunes adolescentes appelées vidomegons issues de milieux sociaux défavorisés qui sont mises au travail très tôt afin de pourvoir aux besoins de leurs familles restées dans les milieux ruraux. Nos recherches nous ont permis de mettre à jour l'insuffisance et le caractère discriminatoire de la réglementation actuelle du travail domestique. Ceci implique qu'il faut revoir la réglementation actuelle afin de protéger ces jeunes travailleuses confinées dans les maisons loin des regards extérieurs qui sont bien souvent confrontées à toutes sortes d'abus. Toutefois, l'adoption par l'OIT en 2011 d'un ensemble de normes qualifiées d'historiques qui vise la protection des travailleuses domestiques a suscité une mobilisation importante et d'importants espoirs au Bénin. Il s'agit de la Convention 189 : Travail décent pour les travailleuses et travailleurs domestiques et de la Recommandation 201. Ces instruments intègrent les travailleuses domestiques dans la réglementation internationale du droit du travail. Ce mémoire propose d'examiner les potentiels apports de cette Convention pour la protection des droits des travailleuses domestiques au Bénin. Dans le cadre de ce travail, nous défendons notamment l'hypothèse que la ratification de la Convention 189 pourrait grandement contribuer à l'amélioration des conditions de vie et de travail des travailleuses domestiques. Nous espérons modestement, que ce travail puisse contribuer à favoriser la mobilisation en faveur de la ratification, par le gouvernement du Bénin, de la Convention 189.
Keywords: Bénin; Conditions de travail; Convention 189; Discrimination; Droit international; Employées de maison; Mobilisation; Organisation internationale du travail; Recommandation (n° 201); Recommandation 201; Travail domestique; Travailleuses domestiques; Vidomègons

Le transport maritime en mer baltique : exemple d'une coopération régionale - Audibert, Élian (Aix-Marseille Université, 2016)

Efficacité de la gestion comptabilité; un levier pour améliorer les performances techniques d'une compagnie d'assurance IARD : Cas de SAHAM assurance Benin - Avoce, Noudéssèwa Modeste (Institut International des Assurances (IIA), 2016)

State interference through domestic courts in international commercial arbitration - Badenhorst, Casper Hendrik Jacobus (University of Johannesburg, 2016)
Keywords: Arbitrage; Arbitragem; Arbitration; International and municipal law; International commercial arbitration

Bilan et perspective de la mise en œuvre des dispositions de l'article 13 nouveau du code CIMA au Burkina Faso : Cas de la générale des assurances - Badini, Roland Rat-Néré (Institut International des Assurances (IIA), 2016)

Les dommages causés aux câbles sous-marins - Bivaud, Alexis (Aix-Marseille Université, 2016)

Les Obligations des Parties au Contrat de Construction navale - Blanco, Rafael (Aix-Marseille Université, 2016)

Comment développer la bancassurance dans le business d'une compagnie d'assurances IARD en zone CIMA? : Cas de SUNU assurance IARD-Centrafrique - Bombard Moundjoutende, Gaétan Cyrille (Institut International des Assurances (IIA), 2016)

Le contrat d’assurance transport maritime de marchandises en Tunisie : reproduction du modèle français - Bousselmi, Rafik (Aix-Marseille Université, 2016)

Le contrat d'assurance transport maritime de marchandises en Tunisie : reproduction du modèle français - Bousselmi, Rafik (Aix-Marseille Université, 2016)

Incidences et difficultés pratiques dans l'indemnisation des préjudices corporels d'acidents de circulation selon les nouvelles dispositions du code CIMA : cas de la CNART - Diallo, Anssoumane (Institut International des Assurances (IIA), 2016)

Micro assurance et rentabilité : Modèle et outils de gestion pour un système pérenne au Tchad - Djounfoune, Elodie (Institut International des Assurances (IIA), 2016)

Assurance crédit-caution, facteur d'émergence économique - Djuidje Kamdem, Isabelle Mélissa (Institut International des Assurances (IIA), 2016)

L'enlèvement des épaves - Dubs, Marine (Aix-Marseille Université, 2016)

Mercenariat et piraterie : vers une privatisation de la protection des navires - El Adraoui, Ayoub (Aix-Marseille Université, 2016)

Le Japon et la chasse à la baleine dans l'antarctique : Licéité, légitimité et résistances - Gallardo, Joséphine (Aix-Marseille Université, 2016)

Cláusulas abusivas en los contratos de préstamo hipotecario. Especial referencia a las denominadas "cláusulas suelo" - García-Serón Atencia, Paloma (Universidad Internacional de Andalucía, 2016)
Trabajo Fin de Curso de Experto Universitario en Derecho Bancario (2014/15). Directora/Tutora: Patricia Márquez Lobillo. El objeto de este trabajo es el examen de la evolución jurídica de las cláusulas abusivas, y en especial de las cláusulas suelo, desde las primeras cuestiones prejudiciales planteadas sobre su legalidad y la posible consideración de abusivas y en consecuencia, nula. He elegido esta temática puesto que se están produciendo muchas modificaciones normativas, doctrinales y jurisprudenciales respecto de las cláusulas que forman parte de los préstamos con garantía hipotecaria. Por ello se ha convertido en un tema de rabiosa actualidad y de continua controversia en Juzgados y Tribunales, por lo que entiendo que es más que necesaria organizar todos los pronunciamientos que se han hecho respecto de estas cláusulas para entender cuándo son consideradas abusivas y por ende, nulas. En primer lugar, he iniciado el proyecto clarificando el concepto de cláusula suelo, seguido de toda la normativa que regula la protección del consumidor así como la trasposición de las Directivas Europeas. Una vez aclarados los conceptos, he analizado la primera sentencia del Tribunal Supremo que se pronunció respecto de la cláusula suelo. En un primer término, me he centrado en explicar los antecedentes de hecho que hicieron llegar al Alto Tribunal a fijar doctrina respecto de las cláusulas suelo. Posteriormente, he analizado la legitimación activa de la asociación de consumidores AUSBANC, que fueron los que promovieron una acción colectiva de cesación de condiciones generales de contratación, en la que solicitaba la declaración de nulidad por tener carácter abusivo, de las condiciones generales de contratación consistentes en las cláusulas de los contratos de préstamo hipotecario a interés variable que establecen un tipo mínimo de interés o un tipo mínimo de referencia solicitando la condena de las demandadas a eliminar dichas condiciones generales de contratación y abstenerse de utilizarlas en el futuro. Seguidamente, he seguido examinando la Sentencia de 9 de mayo de 2013 en cuanto a que es considerada como condición general de la contratación y configuradora del precio del préstamo hipotecario. Así mismo, he explicado la problemática existente en cuanto a la apreciación de oficio de las cláusulas abusivas por parte del órgano jurisdiccional en la normativa española. Particularmente, me he detenido para explicar el doble control de transparencia, que fija la Sentencia de 9 mayo de 2013, que deben superar las cláusulas suelos para ser considerada legales. Respecto de la sentencia de 9 de mayo de 2013, he concluido explicando las dudas respecto de la devolución de las cantidades que no aclaro el Tribunal Supremo en su fallo. De ahí que desde entonces, la interpretación de los Juzgados y Tribunales (jurisprudencia menor) ha sido variada. En vista de ello, el Tribunal Supremo se ha pronunciado de nuevo para aclarar que, cuando en aplicación de la doctrina fijada en su sentencia del Pleno de 9 de mayo de 2013, se declare abusiva y, por tanto, nula una cláusula suelo inserta en un contrato de préstamo con tipo de interés variable, procederá la restitución al prestatario de los intereses que hubiese pagado en aplicación de dicha cláusula a partir del 9 de mayo de 2013. Sin embargo, a pesar de que se ha fijado la irretroactividad de la devolución de las cantidades, existe un voto particular que discrepa el criterio seguido por el Tribunal Supremo en esta sentencia de 25 de marzo de 2015. En vista de las advertencias por parte del Tribunal de Justicia de la Unión Europea así como de la importancia de la Sentencia de 9 de mayo de 2013, España se ha visto obligada a modificar su legislación en trasposición de las Directivas Europeas. En particular, respecto de las cláusulas suelo hay que destacar la importancia de la aprobación de la Ley 1/2013, de 14 de mayo, de medidas para reforzar la protección a los deudores hipotecarios, reestructuración de deuda y alquiler social. Además, en este trabajo se ha pretendido reflejar las dudas que continúan existiendo y que desembocan y probablemente, seguirán desembocando en el futuro en nuevas resoluciones sobre este asunto.

La prérogative de l'arbitre de relever un moyen d'office - Gaucher, Natalia (Aix-Marseille Université, 2016)

Les incidences de la réforme de l'article 13 du code CIMA sur la souscription et la gestion des contrats d'assurances : cas de SAHAM assurances Côte d'Ivoire - Gnangoran, Aman Damien (Institut International des Assurances (IIA), 2016)

La déconstruction des navires - Guillou, Benoît (Aix-Marseille Université, 2016)

Temps de conduite en matière routière : approche juridique - Guiral, Florian (Aix-Marseille Université, 2016)

Le système de contrôle de gestion comme outil de pilotage des sociétés d'assurance de la zone CIMA : Etude de cas de l'africaine des assurances du Bénin - Hounga, Adjimon Achille (Institut International des Assurances (IIA), 2016)

The Interface Between Competition Law and Intellectual Property Law in Kenya - Jerobon, Rotich Caroline (University of Nairobi, 2016)
The interaction between competition law and intellectual property law has often attracted divergent views from scholars and practitioners of each respective sphere of law. Whereas some argue that the two are in conflict with each other and cannot be reconciled. The aforementioned tension between competition law and intellectual property law has been traced to the objectives of each. On the one hand, intellectual property rights confer upon their owners an exclusive right to behave in a particular way while on the other hand competition law strives to keep markets open. Other scholars have argued that, in real sense and practice, the two are actually not in conflict but rather that they complement each other. The question then becomes, is there really an irreconcilable difference between the two areas of law? This paper seeks to establish how the two aspects of law interact and seeks to propose that there be created a balance to alleviate the perceived conflict between the two. This paper will identify the areas in which the balance can be struck. It will also seek to establish how the Kenyan legislative framework as well as the courts has dealt with the conflict. It will proceed from understanding the goals and objective of both intellectual property law and competition law. This will provide the backdrop against which the alleged conflict originates from. A comparative study with other developed jurisdictions will be undertaken so as to advise on the route that should be taken by Kenya on the interface and a conclusion drawn on how the two areas relate and recommendations drawn from the issues identified in the study made.
Keywords: Competencia; Competition law; Intellectual property

La exclusión del socio en la sociedad de responsabilidad limitada - Jiménez Asencio, Juan Manuel (Universidad Internacional de Andalucía, 2016)
Trabajo Fin de Curso de Experto Universitario en Derecho Societario (2014/15). Tutora: Patricia Benavides Velasco. El objetivo del presente trabajo no es más que exponer una síntesis, lo más completa posible, de la materia que nos ocupa, a saber, la exclusión del socio en sociedades de capital, específicamente, en la Sociedad de Responsabilidad Limitada. Se ha pretendido mostrar las distintas perspectivas doctrinales, jurisprudenciales o de otra índole que, a nuestro juicio, hemos considerado más relevantes, posicionándonos argumentativamente junto a aquellas que creemos más acordes con lo que predica la legislación reguladora de la figura estudiada. Se trata de ofrecer una visión global y reflexiva del instituto de la exclusión, tocando todos los aspectos que inciden directamente en ella – al menos eso hemos procurado - , y haciendo especial hincapié en sus causas - punto esencial sobre el que gira la institución - , todo ello sin perjuicio de las humildes opiniones aportadas y reflexiones que pudiéramos plantear, de cuyo riesgo no abjuramos todavía. El resto queda en manos de nuestro lector.

Fiabilité des portefeuilles des compagnies d'assurances non vie à l'épreuve du courtage : Cas du marché ivoirien - Kouadio Beh, Paulin (Institut International des Assurances (IIA), 2016)

Outils de contrôle et de surveillance du portefeuille d'une compagnie de réassurance en zone CIMA : Cas de NCA-RE - Kouadio, Arnaud Stéphane (Institut International des Assurances (IIA), 2016)

La compétence des tribunaux français dans le contentieux du travail maritime - Lecadre, Fanny (Aix-Marseille Université, 2016)

La réassurance vie : Cas de la STAR vie - Ledjibigue, Dono (Institut International des Assurances (IIA), 2016)

Le rôle de la micro finance dans la réduction de la pauvreté dans les pays en voie de développement : cas du Tchad - Levy, Nanque; Mahamat, Haroun Abba (Université Mouloud Mammeri, 2016)
La micro finance vise à permettre aux exclus de système bancaire d’accéder à des services financiers adaptés à leurs besoins, en premier lieu des microcrédits. Mais elle offre aussi la possibilité d’épargner des parts montants, et aussi des systèmes plus développées tels que les services de transferts de fonds et de proposer des instruments de paiement.
Keywords: Développement; Finance; Micro finance; Pauvreté; Produit financier

Les incidences de la modification de l'article 308 du code CIMAsur les activités d'assurances et de réassurance - Libresco K., Ellolia Sandrine (Institut International des Assurances (IIA), 2016)

Análisis jurisprudencial entorno a la impugnación por nulidad en la partición de la herencia - Margallo Toral, Manuel (Universidad Internacional de Andalucía, 2016)
Trabajo Fin de Máster en Derecho Ambiental (2014/15). La partición hereditaria, como cualquier otro acto jurídico puede adolecer de algún defecto o de la ausencia de presupuesto que perturbe sus efectos, pudiendo proceder los coherederos a la evicción y saneamiento de los bienes adjudicados, ex art. 1069 C.C. La sección Cuarta del Capítulo VI del Título III del Libro III de nuestro C. Civil, se ocupa de la “Rescisión de la Partición”, desde el art. 1073 al 1081, tan solo se dedican 9 artículos y de éstos sólo el art 1081, hace referencia a un caso de partición nula. Lo cierto es que el C. Civil no tiene tasadas las causas de ineficacia y nos remite a los principios generales sobre la invalidez de los negocios jurídicos. No hay unas reglas concretas de aplicación cuando surge un vicio o defecto que invalide la partición, con lo cual iremos analizando jurisprudencialmente diferentes posiciones.

Le "Forward Freight Agreement" - Martin, Camille (Aix-Marseille Université, 2016)

Optimisation de la réassurance dans une compagnie d'assurance : Cas Ogar vie - Metou Bekale, Guy Darren (Institut International des Assurances (IIA), 2016)

The resolution of jurisdictional conflicts under the common law and in the European Union - Mlambe, Richard Mike (University of Johannesburg, 2016)
The resolution of jurisdictional conflicts is one of the main functions of private international law. It provided rules to be applied when the courts of more than one country are seized of the same case in international litigation. In determining what that rule should be, regard must be had to the interest of all the relevant entities, namely, the parties to international cases and the courts dealing with such cases. The need to strike a balance is even more urgent in international commercial litigation where the outcome of the case normally has significant economic consequences. From this background, a study has been conducted of two major private international law regimes regarding their approaches to the resolution of jurisdictional conflicts, namely, the common‐law and the European Union (EU). This study is an inquiry into the suitability of each approach in the resolution of jurisdictional conflicts in international commercial cases. It is the view of the present author that each approach has advantages and disadvantages. The common‐law through the doctrine of forum non conveniens shows a greater ability to prevent forum shopping and to prevent injustices in specific cases. However, it is highly unpredictable. On the other hand, the EU approach through the lis pendens rule succeeds in ensuring predictability and certainty in the resolution of jurisdictional conflicts which is very crucial in international commercial litigation. However, its rigidity and inflexibility leads to the determination of international commercial cases by courts that are ill‐suited, thereby giving some room for forum shopping. It is therefore recommended that the two approaches should learn from each other so that their handling of international commercial cases is in line with the special nature of international commercial litigation. The common‐law approach should be made more predictable and the EU approach should allow the courts in the EU to determine which court is best suited to deal with an international commercial case.

The implications of Lagoon Beach Hotel (Pty) v Lehane 2016 (3) SA 143 (SCA) for the South African cross-border insolvency dispensation - Moolman, Shirande (University of Pretoria, 2016)
This mini-dissertation explores the implications of Lagoon Beach Hotel (Pty) Limited v Lehane 2016 (3) SA 143 (SCA) for the South African cross-border insolvency dispensation, as this case deals with the various problems that arise in cross-border insolvency. As a result of these problems and a certain amount of uncertainty when it comes to dealing with cross-border insolvency issues, many investors are reluctant to invest cross-border. This is due to the fact that multiple countries, each with their own laws concerning cross-border insolvency, are involved. Thankfully, the United Nations Commission on International Trade Law has provided a set of guidelines in this regard, namely the Model Law on Cross-Border Insolvency. Although South Africa has enacted the Cross-Border Insolvency Act 42 of 2000, and most of the provisions provided for in the Model law have been included in the legislation, the Act still remains inoperative. Throughout this dissertation the Lagoon Beach case will therefore be critically analysed. The analysis will start off with a discussion of the common law, as it is currently the legal position in South Africa. Thereafter a detailed analysis will be conducted of the various orders of court of the Lagoon Beach case and how the courts differed or agreed in their approach. Finally, the Lagoon Beach case will be discussed in light of the Act and the issues in the case will be solved hypothetically by applying the Act to the problems discussed throughout the dissertation.

Problématique du pilotage des opérations de microassurance en zone CIMA : Cas d'allianz Côte d'Ivoire assurances vie - N' cho Monnin, D. Jean (Institut International des Assurances (IIA), 2016)

The transfer of ownership of movables in the context of international contracts of sale with specific reference to reservation of title clauses : a comparative study - Neibecker, Nadine (University of Johannesburg, 2016)
Please refer to full text to view abstract LL.M. (International Commercial Law)

Maîtrise des risques opérationnels liés au processus de gestion des sinistrés : cas de SAHAM assurance Cameroun - Nguidjol, Jean Félix (Institut International des Assurances (IIA), 2016)

Contribution du réseau indirect dans le chiffre d'affaires et son influence dans le développement des compagnies d'assurance au Congo : Cas de NSIA Congo - Nzaba Mabiala, Guy Palmer (Institut International des Assurances (IIA), 2016)

Pratique de la réassurance et capacité financière des compagnies d'assurances face aux nouvelles contraintes réglementaires : Cas du marché camerounais - Omoko Nkouekoua, Christian (Institut International des Assurances (IIA), 2016)

L'apport d'un réassureur dans le développement de l'industrie de l'assurance en zone CIMA : Cas de la SCG-Ré - Ondo, Igor Mba (Institut International des Assurances (IIA), 2016)

Designing justice: a critical analysis of intellectual property rights within the fashion industry - Parbhoo, Sade (University of KwaZulu-Natal, 2016)
Designers are those individuals within our society with a desire and drive to create. In general designers can be found in all facets of industry and good designers (and ultimately good designs) are the very backbone upon a successful business is built. Designers are required to marry practical knowledge with artistic ability and we are reliant on their skills and to turn abstract ideas into formal designs for everything from the groceries we purchase, the cars we drive and of course, the clothes we wear. Whilst there is no definitive delineation of what a fashion design is, generally fashion designs relate to the creation of designs that focus on clothing, apparel and accessories. The style and functionality of the end products rest firmly within particular time frames, economic and socio-cultural environments within which particular designers find themselves. Accordingly the fashion design industry is never one that stagnates but rather is one that is constantly evolving. In South Africa, the fashion industry is blossoming. As an emerging economy, it is important to create opportunities and not barriers for entry into particular sectors for emerging entrepreneurs. The entire fabric of the fashion industry has certainly changed over time and these changes have brought an increased focus on issues of copying and counterfeiting. It is the contention of some in the industry that there is a need for stricter protection of the actual design in and of itself. Using intellectual property rights as a means of protecting fashion designs is very fitting as every new design begins with an idea, which then evolves, though a process of creative engagement and application of skill and labour to become the final original end product. Designers seeking to protect their designs would need to consider the provisions of the Copyright Act, the Designs Act and the Trade Marks Act. These Acts may in some instances provide a means for protect the actual design incidentally, i.e. by protecting the designer‟s rights in relation to reputation and goodwill associated with the goods whilst in others may afford protection to the design itself. The focus of this research will be a discussion of the legal mechanisms available to fashion designers in South Africa for the protection of their designs using their intellectual property rights and an assessment of whether the fashion industry is in need a stronger intellectual property regime than the current one.
Keywords: Design protection; Fashion industry; Intellectual property; Ownership; Retail trade; South Africa

La définition des risques de guerre et assimilés en assurance maritime et transports et l'adaptation du marché - Patuano, Marine (Aix-Marseille Université, 2016)

La pratique de la sélection et de la tarification des risques en assurance décès emprunteurs : Cas d'Allianz Burkina assurance vie - Rouamba, Pêgdwendé Dénis (Institut International des Assurances (IIA), 2016)

Gestion des sinistrés à payer (SAP) en assurance dommages dans la zone CIMA : Analyse des facteurs d'accumulation et approche de solutions pour leur réduction - Sagna, Messan (Institut International des Assurances (IIA), 2016)

Formation of Contract for the International Sales of Goods - Saleem, Saman Othman (Near East University, 2016)
The Convention for the International Sale of Goods called the Vienna Conference 1980 is an astute international statute that regulates the sale of goods globally. It has been ratified by about 83 countries of the world and countries that have not ratified it have at a point or the other made reference to it. Major economic players apart from England have ratified and have their courts pronounce on the CISG. The Convention provides for the well known elements of contract and also allows for the usage of standard user terms, for example, general terms known or related to certain goods. It is imperial to state that there are also certain regional statutes that are similar to the CISG although with varying differences. It is important to also mention that the CISG also has its lacunae and defects such as allowance for exemption, contents and so on. The CISG has been pronounced upon by courts across the world and has been seen to be highly justiciable.
Keywords: CISG; Convention; English Law; Iraq; United Nations

Le contrat de logistique, un véritable imbroglio juridique - Schoeler, Etienne (Aix-Marseille Université, 2016)

Affected persons in business rescue proceedings : has a balance been struck? - Silangwe, Thandeka (University of KwaZulu-Natal, 2016)
Abstract not available.
Keywords: Buisness enterprises; Business failures; Corporate turnarounds; South Africa

la démarche gestion actif passif dans les compagnies d'assurance de la zone CIMA : cas de SUNU assurance IARD Togo - Siliadin, Komivi Pomégnon (Institut International des Assurances (IIA), 2016)

An analysis of the impact of the sanitary and phytosanitary agreement on market access : case study on the SA/EU citrus dispute and AGOA dispute - Singh, Shikira (University of KwaZulu-Natal, 2016)
Abstract not available.
Keywords: AGOA; African Growth and Opportunity Act; Cooperation Agreement; Market access; Sanitary and Phytosanitary (SPS) Agreement; Trade Development; Trade barrier; WTO; World Trade Organization

la couverture de la responsabilité civile scolaire dans un Etat de la CIMA : cas du Niger - Soumana Hamidou, Abdoul Kader (Institut International des Assurances (IIA), 2016)

La fiscalité applicable à l'activité d'une compagnie d'assurances IARD : cas d' AXA Sénégal - Sy, Mactar (Institut International des Assurances (IIA), 2016)

La gestion actif-passif d'une compagnie d'assurance non vie : Cas de la compagnie d'assurances et de réassurances Sabu Nyumansa - Traoré, Mahamadou (Institut International des Assurances (IIA), 2016)

Les placements des sociétés d'assurance du Mali : Caractéristiques et rendement - Traoré, Mamadou (Institut International des Assurances (IIA), 2016)

Risques et responsabilité civile en matière d'installation pétrolière offshore - Troussier, Julie (Aix-Marseille Université, 2016)

The non-cooperative respondent in international arbitration proceedings : a comparative survey and evaluation of the leading arbitration rules - Venter, Johanlene (University of Johannesburg, 2016)
International arbitration has become accepted worldwide as the principal and, under certain circumstances the preferred method, of resolving international disputes between states, individuals, and corporations in almost every aspect of international trade, commerce, and investment. In general terms, it is expected that an international arbitration procedure is a much speedier method of dispute resolution than formal court proceedings. Although international arbitration holds many benefits for prospective users, there are some difficulties that may arise along the way. An increasingly frequent complaint concerns delays, particularly unconscionable delays and deliberate delaying tactics caused by the parties (i.e. claimant, respondent and/or the arbitrator) which frustrates the process. Arbitration derives from the consent between contracting parties. This implies that the contracting parties gave their consent that a dispute arising from the contract may be resolved by way of arbitration. This will also explain why default by any of the parties is prima facie inconsistent with the consensual nature of arbitration. It is suggested that default during international arbitration is most likely to occur and does not receive the same treatment as the equivalent in the context of formal state court proceedings. Essentially, the objective of this study is to articulate what the claimant can and should do during the arbitral process if and when the respondent is non-cooperative and obstructive in the arbitral process in an attempt to delay and/or destroy the procedure. This study also considers how tribunals should behave in order to promote fairness and the most efficient form of dispute resolution. The research method applied during this study is to conduct a comparative survey and evaluation of the leading arbitration rules available in order to establish what measures are put in place to overcome or mitigate the effects caused by the non-cooperative respondent.
Keywords: Commercial law; International commercial arbitration

Passation de marché et assurances - Yadd, Mass Papa (Institut International des Assurances (IIA), 2016)

La gestion des sinistrés dans une compagnie IARD - Zahe Ibrahim, Aboubacar (Institut International des Assurances (IIA), 2016)

Conciliation des contraintes de gestion technique financière et commerciale en assurance vie dans la zone CIMA : cas de l'union des assurances du Burkina-vie (UAB-vie) - Zongo, Pacome Williams Charlemagne (Institut International des Assurances (IIA), 2016)

دور المحكم في الخصومة التحكيمية - حمودي, سمية (جامعة الوادي university el-oued, 2016)
تناولت هذه الدراسة أهم عنصر من عناصر عملية التحكيم، ألا وهو دور المحكم في خصومة التحكيم، وذلك من خلال معرفة شروط وإجراءات اختاره ومركزه القانوني وسلطاته والتزاماته . و قد بدأت الدراسة بمقدمة تضمنت العناصر الرئيسية للبحث وتناولنا ف الفصل الأول التعريف بالمحكم من خلال بيان معناه وتميزه عن القاضي والخبير والمصالح والوكيل، كذلك بيان الشروط الواجب توافرها في المحكم، كما تم توضيح المركز القانوني للمحكم في خصومة التحكم وكذا بيان طرق تشكيل هيئة التحكيم. كما تناولنا سلطات المحكم، سواء كانت ناشئة عن اتفاق التحكيم، أم المخولة له بموجب القانون، وبيان الالتزامات المرمية على عاتقه أثناء مباشرته لمهمته، وكل ذلك من خلال الفصل الثاني. ومن أهم النتائج التي خلصت إليها الدراسة، هي أن المحكم يتمتع بسلطات واسعة في خصومة التحكيم، إلا أن هذه السلطات الواسعة ليست مطلقة بلا قيود، وإنما يفرض على المحكم عدة التزامات منذ قبوله مهمة التحكيم وحتى صدور الحكم الفاصل في النزاع مرورا بالتزاماته أثناء سير الاجراءات مع مراعاة احترام المبادئ الأساسية للتقاضي. Cette étude portait sur l'élément le plus important du processus d'arbitrage, à savoir le rôle d'arbitre dans l'arbitrage des différends, et grâce à la connaissance des conditions et des procédures choisies statut juridique, pouvoirs et obligations. L'étude a commencé par une introduction comprenait les principaux éléments de la recherche et nous traitée dans le premier arbitre de définition de chapitre à travers les moyens de déclaration et de le distinguer du juge et expert, des intérêts et de l'agent, ainsi que la déclaration des conditions à remplir par l'arbitre, a également clarifier le statut juridique d'un arbitre dans le contrôle des différends, ainsi qu'une description des moyens de la formation du tribunal. Comme nous approchions les autorités de l'arbitre, que ce soit en raison de la convention d'arbitrage, ou qui lui sont conférés en vertu de la loi, et la déclaration des obligations jetées sur lui-même pendant l'exécution de leur mission, et tout au long du deuxième trimestre. Parmi les résultats les plus importants de l'étude, il est que l'arbitre dispose de larges pouvoirs à l'arbitrage des différends, mais ces larges pouvoirs est pas absolue, sans restrictions, mais a imposé à l'arbitre plusieurs engagements depuis accepter la tâche d'arbitrage et jusqu'à la délivrance de l'arbitre décisif dans le conflit par ses obligations au cours de la procédure, avec en tenant compte du respect des principes de base du litige
Keywords: Arbitrage des différends; Arbitration; Arbitre; Obligations de l'arbitre; Pouvoirs de l'arbitre; Statut juridique; Tribunal arbitral; التزامات المحكم; الخصومة التحكيمية; المحكم; المركز القانوني; سلطات و; هيئة التحكيم